2002
DOI: 10.1016/s0893-133x(02)00289-0
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Antipsychotic Drug Treatment Induces Long-lasting Expression of fos and jun Family Genes and Activator Protein 1 Complex in the Rat Prefrontal Cortex

Abstract: We have characterized the effects of chronic clozapine and haloperidol treatments on the expression of fos ( c-fos , fosB , fra-2 ) and jun ( c-jun , junB, junD ) family genes in the rat forebrain. The effects of chronic (17d)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 38 publications
1
28
1
Order By: Relevance
“…However, in contrast to the observations in humans, there were no significant differences in the levels of c-Jun protein in haloperidol-or risperidone-treated rats and controls. A very recent study has shown that chronic 17-day treatment with haloperidol and clozapine increased the expression levels of jun and fos family immediate-early genes in the rat prefrontal cortex using in situ hybridization (Kontkanen et al, 2002). Taken together, these results indicate a differential and brain region-specific regulation of jun and fos genes by antipsychotic drug treatment.…”
Section: Discussionmentioning
confidence: 75%
“…However, in contrast to the observations in humans, there were no significant differences in the levels of c-Jun protein in haloperidol-or risperidone-treated rats and controls. A very recent study has shown that chronic 17-day treatment with haloperidol and clozapine increased the expression levels of jun and fos family immediate-early genes in the rat prefrontal cortex using in situ hybridization (Kontkanen et al, 2002). Taken together, these results indicate a differential and brain region-specific regulation of jun and fos genes by antipsychotic drug treatment.…”
Section: Discussionmentioning
confidence: 75%
“…), calculated as salts, were clozapine, 1.5, 10.0, or 25.0 mg/kg; haloperidol, 1.0 mg/kg; and LSD, 0.24 mg/kg. These doses were selected based on previous findings with clozapine, haloperidol, and LSD in rodent models (Kuoppamaki et al 1993; Kontkanen et al 2002a, b; Gonzalez-Maeso et al 2008; Gray et al 2009). These doses represent approximately 12.5, 3.3, and 0.03 % of the LD50 of clozapine (200 mg/kg), haloperidol (30 mg/kg), and LSD (800 mg/kg) after i.p.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that extinction of fear may be compromised in these disorders (Charney, 2004). Interestingly, longterm treatment with anti-psychotic medications in rats increased the levels of c-Fos in the mPFC (Kontkanen et al, 2002), suggesting that these drugs may stimulate an endogenous fear-reduction system. A better understanding of molecular mechanisms of fear extinction could lead to new pharmacological treatments for anxiety disorders targeting the mPFC.…”
Section: )mentioning
confidence: 99%